2012
DOI: 10.1089/apc.2011.0432
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Combination HIV Prevention Strategy: Post-Exposure Prophylaxis with Contingency Management for Substance Abuse Treatment Among Methamphetamine-Using Men Who Have Sex with Men

Abstract: Methamphetamine use has been associated with HIV transmission among men who have sex with men (MSM). However, providers have been hesitant to utilize post-exposure prophylaxis (PEP) in populations of stimulant users. This single-arm, open label pilot study sought to demonstrate the safety, feasibility, and acceptability of PEP combined with the drug abstinence intervention of contingency management (CM) in methamphetamine-using MSM. HIV-uninfected MSM reporting recent methamphetamine use were recruited to a CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 44 publications
2
34
0
5
Order By: Relevance
“…(20) It is likely that the use of PrEP by MSM who use other stimulants, such as crystal methamphetamine, may have similar effects. It has been well established that crystal methamphetamine and cocaine use are associated with higher-risk sexual behavior and incident HIV infection,(5,7,10,12,21) and previous studies have shown stronger associations between stimulant use and serodiscordant condomless anal intercourse than with alcohol use. (22) Stimulant users may therefore be particularly good candidates for PrEP, and understanding perceived barriers and facilitators to uptake and adherence may improve effectiveness of PrEP implementation programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(20) It is likely that the use of PrEP by MSM who use other stimulants, such as crystal methamphetamine, may have similar effects. It has been well established that crystal methamphetamine and cocaine use are associated with higher-risk sexual behavior and incident HIV infection,(5,7,10,12,21) and previous studies have shown stronger associations between stimulant use and serodiscordant condomless anal intercourse than with alcohol use. (22) Stimulant users may therefore be particularly good candidates for PrEP, and understanding perceived barriers and facilitators to uptake and adherence may improve effectiveness of PrEP implementation programs.…”
Section: Discussionmentioning
confidence: 99%
“…(7,12) Since optimal adherence is required to achieve PrEP efficacy and subsequently decrease risk of HIV acquisition, substance use could limit the effectiveness of PrEP if substance using MSM are unable to take PrEP as prescribed. Although prior studies have suggested that stimulant use did not affect PrEP adherence(16), in the current study substance users expressed concern about their ability to adhere to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although consistent condom use remains an essential HIV prevention strategy even in the context of PrEP (13), daily oral PrEP, which does not rely on event-specific adherence, may be a more feasible risk reduction strategy for methamphetamine using MSM with non-main partners. Available data do not support concerns that biomedical HIV prevention strategies, such as PrEP, cannot be successfully implemented with people who use drugs (37,38). …”
Section: Discussionmentioning
confidence: 99%
“…Given the potential for PrEP and PEP to reduce the acquisition of HIV infection among sex workers, MSM and people who use and inject drugs (Izulla et al 2013; Landovitz et al 2012; Mack et al 2014; McGowan 2014), future research should be conducted to examine the feasibility of these interventions in this setting.…”
Section: Discussionmentioning
confidence: 99%